(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to: 1- Knowing the level of self-awareness among students of the Institute of Fine Arts for Girls. 2- Knowing the significance of the differences in self-awareness among the students of the Institute of Fine Arts according to the grade variable. In light of the findings of the researcher in the current research, the following can be concluded: 1- The female students are characterized by self-awareness, as their non-normative level was higher than the average, which indicates a high self-awareness among the students of the Art Institute. 2- The level of self-awareness increased with age, as there was a difference between (first grade and third grade) and in favor of the third grade.